
分解因式:(a+b)(a-b)-4(b+1)
4个回答
展开全部
=a²-b²-4b-4
=a²-(b²+4b+4)
=a²-(b-2)²
=(a+b-2)(a-b+2)
=a²-(b²+4b+4)
=a²-(b-2)²
=(a+b-2)(a-b+2)
展开全部
原式=a^2-b^2-4b-4
=a^2-(b^2+4b+4)
=a^2-(b+2)^2
=(a+b+2)(a-b-2)
=a^2-(b^2+4b+4)
=a^2-(b+2)^2
=(a+b+2)(a-b-2)
已赞过
已踩过<
评论
收起
你对这个回答的评价是?
2011-10-16
展开全部
=a^2-b^2-4b-4
=a^2-(b^2+4b+4)
=a^2-(b+2)^2
=(a-b-2)(a+b+2)
=a^2-(b^2+4b+4)
=a^2-(b+2)^2
=(a-b-2)(a+b+2)
已赞过
已踩过<
评论
收起
你对这个回答的评价是?
2011-10-16
展开全部
=a^-b^-4b-4=a^-(b-2)^=(a+b-2)(a-b+2)
已赞过
已踩过<
评论
收起
你对这个回答的评价是?
推荐律师服务:
若未解决您的问题,请您详细描述您的问题,通过百度律临进行免费专业咨询